2023
DOI: 10.1186/s12916-023-02793-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between an inflammatory diet index and severe non-alcoholic fatty liver disease: a prospective study of 171,544 UK Biobank participants

Abstract: Background Although non-alcoholic fatty liver disease (NAFLD) is linked to inflammation, whether an inflammatory diet increases the risk of NAFLD is unclear. This study aimed to examine the association between the Energy-adjusted Diet Inflammatory Index (E-DII) score and severe NAFLD using UK Biobank. Methods This prospective cohort study included 171,544 UK Biobank participants. The E-DII score was computed using 18 food parameters. Associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…For example, utilizing the data from NHANES 2005-2016, Zhang et al found that a pro-inflammatory diet as measured by the Dietary Inflammatory Index (DII) was associated with a deteriorating NAFLD, where participants in the highest quartile of DII scores had a significantly 52% higher risk of NAFLD than the lowest quartile [31]. Similar results were identified among UK Biobank participants, Petermann-Rocha et al revealed a significant association between the E-DII (Energyadjusted Diet Inflammatory Index) and incident severe NAFLD by resulting that individuals in the very pro-inflammatory category had 1.54 times higher risk of severe NAFLD compared with those in the very anti-inflammatory group [32]. While inversely E-DII (indicating an anti-inflammatory diet) was correlated with lower US fatty liver index and hepatic steatosis index values in a nationally representative sample of US adults [33].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For example, utilizing the data from NHANES 2005-2016, Zhang et al found that a pro-inflammatory diet as measured by the Dietary Inflammatory Index (DII) was associated with a deteriorating NAFLD, where participants in the highest quartile of DII scores had a significantly 52% higher risk of NAFLD than the lowest quartile [31]. Similar results were identified among UK Biobank participants, Petermann-Rocha et al revealed a significant association between the E-DII (Energyadjusted Diet Inflammatory Index) and incident severe NAFLD by resulting that individuals in the very pro-inflammatory category had 1.54 times higher risk of severe NAFLD compared with those in the very anti-inflammatory group [32]. While inversely E-DII (indicating an anti-inflammatory diet) was correlated with lower US fatty liver index and hepatic steatosis index values in a nationally representative sample of US adults [33].…”
Section: Discussionsupporting
confidence: 55%
“…Diet plays an important role in NAFLD development [28,29], and the underlying mechanisms are suggested to partially involve the modulation of inflammation [30,31]. Regarding the association between diet and NAFLD, a few prior studies have examined this association using different approaches: either inflammatory diet index or empirically derived dietary patterns [31][32][33][34]. For example, utilizing the data from NHANES 2005-2016, Zhang et al found that a pro-inflammatory diet as measured by the Dietary Inflammatory Index (DII) was associated with a deteriorating NAFLD, where participants in the highest quartile of DII scores had a significantly 52% higher risk of NAFLD than the lowest quartile [31].…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of this study is severe NAFLD, which was obtained via links to the hospital and death record. NAFLD was identified with International Classification of Diseases-10 (ICD-10) codes K75.8 and K76.0 according to previous studies [ 21 , 28 , 29 ] (see Table S 2 for details).…”
Section: Methodsmentioning
confidence: 99%
“…The establishment of DII provided a valuable method to assess the effect of dietary inflammatory potential on health. DII is found to be strongly associated with many health outcomes, such as cardiovascular disease (CVD), non‐alcoholic fatty liver disease, cancer and neurodegenerative diseases 7–9 . Surprisingly, only a few studies delved into the association between DII and the risk of diabetes, and the results varied 10–14 .…”
Section: Introductionmentioning
confidence: 99%